Prospective oversight and approval of assisted dying cases in Victoria, Australia: a qualitative study of doctors’ perspectives - White, Ben P; Willmott, Lindy; Sellars, Marcus; Yates, Patsy (BMJ supportive & palliative care, 2024)
BackgroundAssisted dying (AD) is increasingly becoming lawful internationally. While all AD models have oversight mechanisms, Victoria, Australia is rare in requiring formal approval before AD is permitted. Other jurisdictions are now enacting or implementing prospective approval models yet little is known about their operation. This paper reports the first empirical research internationally analysing the operation of a prospective approval model.MethodsThis qualitative study recruited doctors involved in providing lawful AD during the first year of the Victorian AD system. Recruitment occurred through the mandatory training doctors providing AD must undertake. Semistructured interviews were undertaken predominantly through Zoom conferencing, transcribed and thematically analysed.Results32 doctors from diverse specialties (including general practice) and diverse AD experiences were interviewed. Six themes were identified: (1) The primary gatekeeping to AD in practice was by the administrative Secretariat of the oversight body, the Voluntary Assisted Dying Review Board, and not the government department who issues the final ‘permit’; this may not have been intended by parliament. (2) The prospective oversight and approval process was bureaucratic and (3) the mandatory online system to manage AD was a barrier. (4) These factors caused unnecessary delays which (5) impeded AD for very sick patients. (6) However, this prospective process protected doctors and ensured system safety.ConclusionsPotential barriers to accessing AD posed by prospective approval should be evaluated carefully by jurisdictions implementing or considering such a model. Attention is needed not only to law but to system design and how AD is implemented in practice.